Revealing Hidden Syntax in Olivia Rodrigo’s Traitor: A Tree Diagram Analysis of Verb Phrases - Maylinda, Cindy; Nurhapitudin, Irman; Sariyati, Ice (Universitas Pahlawan Tuanku Tambusai, 2025)
Syntax is crucial for understanding the structure of language, including verb phrases. While research into syntactic structures has been done in several texts, there is limited focus on modern song lyrics, particularly in the context of syntactic tree representation. This research looked into the syntactic patterns of verb phrases found in Olivia Rodrigo's song Traitor using the Chomsky Tree Diagram method. A qualitative descriptive approach classifies the verb phrase into intransitive, mono transitive, ditransitive, complex transitive, and intensive types. This research applies TGG to the data, comprising of the verb phrases extracted from the lyrics, which are illustrated as tree diagrams. The findings of this study have shown different forms of the structure of verb phrases and their hierarchical relationship existing within the lyrics. The given study contributes to the syntactic research by pointing out the importance of verb phrase analysis in modern textual forms.